The Analysis of Language Style Used in Indonesian Stand-Up Comedy Shows - Amirul Azhar; Fitrawati Fitrawati (English Language and Literature, 2023)
This study aimed to analyze the use of language style in Indonesian stand-up comedy show. The researcher used Martin Joss’s theory in 1967 about five styles of language in form of formality; frozen style, formal style, consultative style, casual style and intimate style. This study analysis what are the types and the most frequent style that are used in the Indonesian stand-up comedy shows. The form of research used is qualitative descriptive approach. The data in this research obtained from the five videos of Ridwan Remin stand-up comedy in YouTube. The result showed that there were three styles used in those videos. They were frozen style, formal style and intimate style. After the researcher counted the data, the most frequent style was the casual style with 93.96% of whole utterances. It is concluded that the use of casual style was the characteristics of Ridwan Remin in delivering humor material.